Eradication of Corruption Crimes Based on Pancasila Values by Revitalizing and Re-actualizing Pancasila - Listiani, Ririn Ayu (Universitas Negeri Semarang, 2018)
Corruption that has happened for a long time in this country has not been able to be resolved. In all comparative studies of eradicating corruption between countries, Indonesia always occupies the lowest position. The high number of corruption in Indonesia needs to be taken seriously to eradicate corruption in Indonesia. However, until now the eradication of corruption in Indonesia has not shown a bright spot. Although there are rules and laws for acts of corruption, but still not able to overcome this problem, because corruption has become a rooted cultural system also becomes a nation-style life. So it is indeed quite difficult to eliminate corruption in Indonesia. Therefore, it is necessary to reconstruct the mindset, lifestyle, and morality of a nation by exploring the values of Pancasila as the planting of character, behavior and personality for Indonesian people from an early age. It is very important to revitalize the values of Pancasila when this nation suffers from bad morals, because revitalization is a real effort to reconstruct and replace the nation's morality in the right position when it has gone far beyond the values of national morality namely Pancasila. Pancasila revitalized the function and occupation of Pancasila as a philosophy of good nation and state. And make the source of all sources of law in the country of Indonesia. So that the revitalization of Pancasila is very important for Indonesian guidelines in the life of the nation and state.